The Visual and Instrumental Analyses of Different Single-Shade Resin Composites - Erçin, Özlem (2023)
The purpose of this study was to evaluate the color adaptation of single-shade resin composites applied to different tooth shades. A total of 108 class III preparations (n=6) were performed on the acrylic denture maxillary incisors (2mm depth and 2mm height). 5 single-shade resin composites (Vittra APS Unique, Omnichroma, ZenChroma, Clearfil Majesty ES-2 Universal, Charisma Topaz One) and 1 multishade resin composite (Estelite Asteria) were placed in the cavities and polished. I performed visual and instrumental color analyses. The CIEDE2000 formula was used to assess the shade differences (∆E) between teeth and restorations. The obtained ∆E values were recorded and statistically analyzed. For the instrumental analysis, ZenChroma in A1 shade groups showed statistically significant higher differences (p<0.05). Among all tested materials, A3 shade groups showed lower ∆E values (p<0.05). For the visual analysis, there were no significant differences between materials and scores in A1 and A3 shade groups (p>0.05). There were statistically significant differences between the materials and the scores in A2 shade groups (p<0.05). As a result of this study, it was concluded that, making esthetic restorations with single-shade resin composites promises proper color adaptation, but their properties still need improvement. Single-shade resin composites can reduce chair-time and technical sensitivity with good color matching.